Test Results of Winter Wheat Varieties in 2002/2003 in the Hajdusag - Ágoston, Tamás; Pepó, Péter (Acta Agraria Debreceniensis, 2004)
We examined 35 early, 32 mid-season and 12 mid-late winter wheat varieties on calciferous chernozem soil after sunflower green crop in 2003. We set-up the experiment on small-size parcels, with 4 repetitions. In addition to the favourable agrotechnical conditions, with this year’s extreme ecological conditions the varieties resulted in weaker yields (2500-3200 kg/ha). Our findings have proven that there is a significant difference both between the maturity groups and between the yield potential of varieties with different genotypes, inside each group. Early varieties showed lower yield potentials according to the other two groups. The differences between the various variety’s yields was the smallest in the mid late group (893 kg/ha). Under given ecological and agrotechnical conditions, the following varieties showed the relatively best yields and best adaptability:• early maturing varieties (3200-3700 kg/ha): Mv palotás, KG Magor, Mv Mambo, Mv Emese, GK Margit, GK Tündér, GK Csongrád, GK Attila, Mv Amanda, Ukrainka;• mid season varieties (3300-3800 kg/ha): Győző, GK Marcal, Róna, GK Rába, Buzogány, MF Kazal, GK Mura, Hunor, GK Cipó, Mv Magvas, Mv Vilma, GK Zugoly, Jubilejnaja 50;• mid-late varieties (3200-3600 kg/ha): Maximus, Complet, KG Kunhalom, GK Holló.